Neuroligins Nlg2 and Nlg4 Affect Social Behavior in Drosophila melanogaster - Corthals, Kristina; Heukamp, Alina Sophia; Kossen, Robert; Großhennig, Isabel; Hahn, Nina; Gras, Heribert; Göpfert, Martin C.; Heinrich, Ralf; Geurten, Bart R. H. (Frontiers in Psychiatry, 2017)
The genome of Drosophila melanogaster includes homologs to approximately one third of the currently known human disease genes. Flies and humans share many biological processes, including the principles of information processing by excitable neurons, synaptic transmission and the chemical signals involved in intercellular communication. Studies on the molecular and behavioural impact of genetic risk factors of human neuro-developmental disorders (autism spectrum disorders, schizophrenia, attention deficit hyperactivity disorders and Tourette syndrome) increasingly use the well-studied social behaviour of D. melanogaster, an organism that is amenable to a large variety of genetic manipulations. Neuroligins are a family of phylogenetically conserved postsynaptic adhesion molecules present (among others) in nematodes, insects and mammals. Impaired function of neuroligins (particularly of neuroligin 3 and 4) has been associated with autism spectrum disorders in humans and impaired social and communication behaviour in mice. Making use of a set of behavioural and social assays we here analysed the impact of two Drosophila neuroligins Dnlg2 and Dnlg4, which are differentially expressed at excitatory and inhibitory central nervous synapses, respectively. Both neuroligins seem to be associated with diurnal activity and social behaviour. Even though deficiencies in Dnlg2 and Dnlg4 appeared to have no effects on sensory or motor systems, they differentially impacted on social interactions, suggesting that social behaviour is distinctly regulated by these neuroligins.